Acquired Ophthalmoplegia in Older Children and Adults. Issue 1 (2nd January 2018) - Roper-Hall, Gill
ABSTRACT: Ophthalmoplegia or ophthalmoparesis are the terms given to paralysis or paresis of one or more of the extraocular muscles in one or both eyes. It may be representative of serious neurological or systemic disease. Other mechanisms may cause limitation of eye movement, including restrictive or myasthenic conditions, or combinations of several etiologies. Evaluating and differentiating the mechanisms causing ophthalmoplegia is important in determining the correct diagnosis and selecting the appropriate management in these complex cases.